Avaliação de clusters da composição química do leite no Estado de Goiás - Brasil, Rafaella Belchior (2016)
The dairy husbandry is one of the economic activities that most stands out in the state of Goiás; it plays an important role in food supply, generating employment and income for the population. The understanding of the use of tools that incorporate geographic attributes related to herd location and milk quality indicators can be explored in geostatistical terms for the analysis and identification of areas (territories) with similar spatial characteristics. Thus, studies to identify clusters, may indicate the establishment of regional differences and assist in cattle management in these regions. This study aimed to evaluate the chemical quality of refrigerated milk and the occurrence of clusters of chemical composition of refrigerated milk from the Mesoregions the state of Goiás in the rainy and dry periods during the years 2011 to 2014. We evaluated 17,393 data of milk chemical composition extracted from the database of the Milk Quality Laboratory /CPA/EVZ/UFG. We adjusted a Multiple Linear Regression to verify whether year, period, and mesoregion exerted influence on milk components and we used Wald test to verify the significance of the model coefficients. For the preparation of the spatial distribution maps of milk chemical composition, we used geostatistical resources which followed kriging data interpolation method. To identify clusters that represent the geographic information grouped into similar values, we used the GIS ArcGIS 10.1® with Cluster and Outlier Analysis tool (Anselin Local Moran's I) contained in the Spatial Statistic tool. The chemical composition of milk had seasonal and regional behavior, being relatively higher in the dry season (fall/winter) and denser in traditional dairy regions. In the period of lower humidity and temperature the percentages of fat, protein, TDE, and DDE were the most intense in the period of higher humidity and temperature. Lactose showed antagonistic behavior to other milk components in relation to seasonality; in the rainy season, the lactose content was higher. We found significant formation of clusters in the state, especially in the most productive regions. Spatial analysis of the dairy chain of Goiás showed milk production is concentrated mainly in the southern portion of the state, a fact that attests to the importance of industry production in this region. Seasonality of milk production is a major issue for the dairy sector as it affects milk production and composition, as well as the price paid to the producer. The progress achieved by the State still faces many challenges and obstacles to continue growing and developing; therefore, it is necessary and important to carry out further studies to guide the work of the entire chain, and the adopt of geoprocessing tools that can support policies for the dairy sector, including improving the efficiency of the activity.